The Diagnostic Value of Angiotensin, γ-GT, Blood Lactate, and Renal Resistance Index Combined Detection in Acute Kidney Injury After Neonatal Asphyxia: Combined Angiotensin, γ-GT, Lactate, and RRI in Neonatal Post-Asphyxia AKI - Shi, Xiaoqing; Liying Dai, Liying; Ying Wang, Ying; Fang Deng, Fang (Journal of Medical Biochemistry, 2025)
Background: To investigate the diagnostic value of angiotensin (Ang), gamma-glutamyltransferase (γ-GT), blood lactic acid and renal resistive index (RRI) for acute kidney injury (AKI) after neonatal asphyxia. Methods: A total of 120 asphyxiated neonates admitted to the hospital from May 2021 to April 2024 were retrospectively selected. According to whether AKI occurred after asphyxia, the neonates were divided into AKI group and non-AKI group. The occurrence of AKI in neonates with different degrees of asphyxia was analyzed. Plasma Ang-I and Ang-II levels and urine γ-GT level were compared between the AKI group and the non-AKI group. The blood gas analyzer was used to determine blood lactic acid levels and color Doppler ultrasound was used to evaluate RRI. The correlation between blood Ang, urine γ-GT, blood lactic acid, RRI and serum creatinine (Scr) and blood urea nitrogen (BUN) was discussed. Multivariate logistic regression model was used to identify factors influencing the occurrence of AKI after neonatal asphyxia. The receiver operating characteristic (ROC) curve was used to evaluate the diagnostic efficacy of relevant indicators for AKI after neonatal asphyxia. Results: Among the 120 asphyxiated neonates, the incidence of AKI was 39.17% (47/120). The incidence of AKI was significantly higher neonates with severe asphyxia than in those with mild asphyxia (P
Keywords: Neonate; Asphyxia; Acute kidney injury; Angiotensin; Gamma-glutamyltransferase; Blood lactic acid; Renal resistive index